Scholar dropout: circumstances that describe the moment of early school leaving (Revista INTEREDU11, 2021)
The topic in this article addresses the factors associated to dropout. For this study we will understand as equivalent the concepts of abandonment and desertation. The dropout is understood as the temporary or definitive abandonment of the education system by a compulsory-education student (CEOC, 2009). The objective of this article consists in the description of varied circumstances surrounding daytime-school dropout, in students that had abandoned daytime primary or secondary schools to continue studying in the Young and Adult Education Program (EDJA for its acronym in Spanish) at ‘Colegio Emprender Osorno’. The research methodology used in this article is quantitative (Hernandez, Fernandez y Baptista 2003), and the sample has been formed by 85 students who did abandon the regular-daytime education system, and that at the moment of this study were already into the EDJA. The instruments used for the gathering of information was a questionnaire made by close questions. The results allow us to acknowledge that the circumstances surrounding the moment of scholar withdrawal are multifactorial, and they are usually linked to a family context, academic success and socioeconomic issues.